(3JMaI GdCHQGQ aj eYQaI GdCbVjI hGdCbOGQs - (3GdbWjaj, YHO Gddg Hf aQL Hf YHO Gddg Hf YeQGf, J (B1160(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj Mce HhLhO eG jQjO hLhOg(B... (3hHYO(B... (3Efj CdajJ LeGYI ef GdeSdejfs
(3BNQgG (B:s
(3heYfi NOGY Gddg EjGge aj bhdg JYGdi(B: (3hgh NGOYge, eLGRGJg dge Ydi NOGYge(B... (3Ydi eG aYdhg aj gPg GdOGQ ef GdcaQ hGdeYGUj(B. (3hdjcf gPG BNQ eG CQOfG EjQGOg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI Qbe(B: 1455s
(3GdPQjYI Qbe(B: 1455s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds